1998
DOI: 10.1029/98jb00593
|View full text |Cite
|
Sign up to set email alerts
|

The thermal structure of collisional orogens as a response to accretion, erosion, and radiogenic heating

Abstract: Abstract. Thermal models of collisional orogens generally predict temperature structures that are much cooler than those recovered by thermobarometric studies. Here we demonstrate that hightemperature, low-pressure metamorphism and the development of inverted geotherms within collisional belts may be the result of accretion and erosion acting on crust enriched with heatproducing elements. A new two-dimensional finite difference model, described here, incorporates the subduction of lithosphere with heat-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 51 publications
1
118
1
Order By: Relevance
“…11a), from 340 to at most 314 Ma, developed at temperatures above the water-saturated quartz -feldspar solidus and was coeval with crustal thickening characterized by (a) thrusting of the Upper Gneiss Unit at the roof and margin of the dome, (b) decoupling and stacking of the Lower Gneiss Unit preserved within the migmatites, and (c) metamorphic paragenese of the Cévennes micaschists (Arnaud, 1997). At this stage, thermal relaxation and heat production within the thickened crust were probably the main causes of temperature increase (England and Thompson, 1984;Huerta et al, 1998). The emplacement of the peri-Velay precursor granites and high-K magnesian monzodiorite magmatism of mantle origin constitute an additional heat source.…”
Section: Discussion: the Significance Of Crustal Anatexis In The Velamentioning
confidence: 99%
See 1 more Smart Citation
“…11a), from 340 to at most 314 Ma, developed at temperatures above the water-saturated quartz -feldspar solidus and was coeval with crustal thickening characterized by (a) thrusting of the Upper Gneiss Unit at the roof and margin of the dome, (b) decoupling and stacking of the Lower Gneiss Unit preserved within the migmatites, and (c) metamorphic paragenese of the Cévennes micaschists (Arnaud, 1997). At this stage, thermal relaxation and heat production within the thickened crust were probably the main causes of temperature increase (England and Thompson, 1984;Huerta et al, 1998). The emplacement of the peri-Velay precursor granites and high-K magnesian monzodiorite magmatism of mantle origin constitute an additional heat source.…”
Section: Discussion: the Significance Of Crustal Anatexis In The Velamentioning
confidence: 99%
“…According to current petrological and thermal numerical models (Thompson and Connolly, 1995;Huerta et al, 1998), a simple crustal thickening event followed by erosion can hardly account for the generation of large volumes of granite. Results from experimental petrology show that high melt fractions require conditions well above 800°C, above the destabilization curves of hydrous minerals (Clemens and Vielzeuf, 1987;Patiño Douce and Johnston, 1990;Gardien et al, 1995).…”
Section: Discussion: the Significance Of Crustal Anatexis In The Velamentioning
confidence: 99%
“…(3) Advective heat transfer to the upper crust by exhumation of hot eclogitic slices within a subduction channel (becker 1993; Engi et al 2001), or alternatively, by extension-related exhumation of hot high-pressure rocks (Platt 1986;ballèvre et al 1990). (4) Accretion of continental crustal rocks characterised by high radioactive heat production (chamberlain & sonder 1990;bousquet et al 1997;Huerta et al 1998;roselle et al 2002;Goffé et al 2003).…”
Section: Discussion Of Potential Heat Sources Of Barrow-type Overprinmentioning
confidence: 99%
“…However, using realistic crustal properties, it has also been suggested that thrusting could not be responsible for inverted gradient beneath thrusts (e.g. Jaupart and Provost, 1985;Ruppel and Hodges, 1994;Huerta et al, 1996Huerta et al, , 1998 but only induces low thermal perturbations (Shi and Wang, 1987;Endignoux and Wolf, 1990).…”
Section: Thrust Propagationmentioning
confidence: 99%